Investigation and modernization of buckets of surface mining machines. (1st May 2015) - Rusiński, Eugeniusz; Cegiel, Lesław; Michalczyk, Andrzej; Moczko, Przemysław; Olejarz, Jerzy; Pietrusiak, Damian
Highlights: Long term experimental testing of the bucket wear. Analysis of the bucket–soil interaction. Economical analysis. Structural analysis and optimization of the buckets. Abstract: The article presents the results of experimental tests, design work and numerical analyses aimed at optimizing the operating costs of buckets used in the Turów Lignite Mine. The presented approach to designing and optimization takes into consideration the results of tests in real mining conditions as well as modern numerical tools that support the process of designing such structures. The results of the presented work include two buckets with quickly replaceable and permanent teeth, which significantly improve the technical and operational indicators and enable their users to achieve real savings.